Evaluation Of Cassava Stem Based Activated Carbon As Potential Waste Water Treatment Adsorbent - Sulaiman, Nurul Syuhada (2018)
The main purpose for this study is to investigate the potential of cassava stem to be utilized as a low cost precursor in activated carbon production. The cassava stem was converted to the activated carbon by self-activation process. The optimum activation parameters were determined by using Response Surface Methodology programme. The potential of activated cassava stem as adsorbent was further examined through surface modification with sodium hydroxide, calcium chloride and zinc chloride with concentrations of 0.5 M and 2.0 M. The activated and surface modified activated cassava stem were then employed in liquid phase adsorption of methylene blue dye and ofloxacin antibiotic with raw cassava stem as comparison. The characteristics of raw, activated and surface modified activated materials were analysed including the content of fixed carbon, volatile matter, ash, holocellulose, and lignin. All types of cassava stem adsorbents were then analysed using surface area analysis, Elemental analysis, Scanning Electron Microscopy, Energy Dispersive X-ray, pH at zero point charge, Fourier Transform Infrared Spectroscopy, Thermogravimetric Analysis and X-ray Diffractometry Analysis. Batch adsorption studies, thermodynamic studies, kinetic studies and isothermic studies were done to examine the adsorption capacity and behaviour of the adsorbents at different conditions. The results on the characteristics of raw cassava stem showed that the cassava stem is suitable to be converted into the activated carbon with higher surface area and yield while the activated cassava stem characteristics indicated that the activated form possesses better properties to serve as a good adsorbent than its raw form.